Charm and the standard model - Sheldon Lee Glashow (Nuclear Physics B)
This is a very personal account of the evolution of the Standard Model of Particle Physics, as I experienced it, from the years 1954 to 1976. I highlight the theoretical prediction of the charmed quark and the experimental discovery of the J particle.